Sample-size requirements for accurate length-frequency distributions of mesophotic reef fishes from baited remote underwater stereo video. (March 2021) - Arachchige Weerarathne, Illangarathne; Monk, Jacquomo; Barrett, Neville
Highlights: Between 60 and 120 individuals are needed to accurately reflect the fish size structure. Between 20 and 2000 independent baited stereo camera deployments are required. Number of individuals and deployments differed between species. Methods aid researchers to better refine overall sampling effort. Abstract: Accurate descriptions of size structure are important for adaptive management of marine fish populations subject to anthropogenic and environmental pressures. This requires monitoring programs that can measure the length of enough individuals within each focal fish population. This study assessed the number of length measurements required to accurately describe the size structure in a range of common mesophotic demersal fish species observed from baited remote underwater stereo video (stereo BRUV) sampling programs. Here, we use a resampling approach from an empirical length dataset collected as a part of ongoing monitoring efforts to characterize mesophotic reef fish assemblages across the continental shelf of eastern and southern Tasmania, Australia. The results suggest that, on average, between 60 and 120 individuals length measurements are needed from at least 20 to 2000 independent deployments to be 95% confident that samples reflected the "real" size structure of fishes captured using stereo BRUVs. It is important to note that the "real" size-structure of each fish species here is unknown but was parameterized by pooling all measurements across the stereo BRUV dataset. It should also be noted that the exact number of length measurements differs across species, with some less abundant species requiring substantial sampling effort. This study helps to inform initial sampling requirements for length measurements for monitoring programs using stereo BRUVs. It provides a methodology that can aid researchers to further refine the overall sampling effort for future fisheries and marine park monitoring applications.